Existential Security in Technogenic Culture - Baeva, Liudmila V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2025)
The research is addressed to the study of existential security, which is becoming one of the universal values in the modern world and an interdisciplinary concept for a wide range of philosophical, social, political, cultural sciences. A comprehensive analysis is proposed regarding both the concept of existential security itself and the study of a wide range of factors related to the actualization of the problem of existential risks and threats in the modern world. The main research approaches to the understanding of existential security in the world and Russia are summarized, their orientation and content are shown. The refined definition of existential security is proposed from the position of integrative ontological, anthropological and axiological approaches, which allows to combine and take into account the possibilities of the prevailing approaches in science and supplement them with the parameters associated with modern risks, threats and challenges, including potential and real ones. The ontological, anthropological, ethical, social, technological aspects of existential security are identified and characterized. The trends in the assessment of existential threats and factors of protection from them in modern society are revealed, the levels of manifestation of existential challenges in the conditions of technological transformation, pandemic of new coronavirus infection, open military confrontation between Russian civilization and the Collective West and hidden directed destructive impact through ethnoreligious determinants are shown. The study from the position of existential approach characterizes the most pressing threats, shows their destructive potential for present and future generations, social relations and the inner self, which is subject to deformation through the propaganda of aggressive behavior patterns.